Grutas y altares moralizados. O de cómo territorializar las muertes violentas en sectores populares (Córdoba, Argentina) - Natalia Bermúdez (Corpus: Archivos Virtuales de la Alteridad Americana, 2019)
Within the framework of the proliferation of altars, murals and memorials in the popular sectors of Cordoba built to honor young people killed in contexts of violence, in this article I propose to analyze how altars and memorials are established in some way as “portals” of the margins, that is, as moralized territories where the popular groups deal with death, dispute the senses that society destines for their dead and appeal to conventional values to do so. By virtue of degrading daily experiences throughout their life trajectories but particularly after a death or disappearance, families assume, reflect, answer and question those moral disputes that cross their cases. The fact that these groups appeal to conventional values does not imply that it is only on pursuit of universalizing their claims, and far from responding linearly to the reputation that the hegemonic sectors hold of them, such values are part of their experiences and fall within their expectations and possible horizons. And what a ritual passage, buth death, to enroll that person within socially known and legitimated frameworks and parameters. This paper is the result of an ethnographic investigation that I have been developing since 2007 and of intervention activities between the university and different organizations with relatives of victims for the creation of an itinerant sample of images.